Engineered P450 biocatalysts show improved activity and regio-promiscuity in aromatic nitration - Ran Zuo; Yi Zhang; Chao Jiang; John C. Hackett; Rosemary Loria; Steven D. Bruner; Yousong Ding (Scientific Reports, 2017)
Abstract Nitroaromatics are among the most important and commonly used chemicals but their production often suffers from multiple unsolved challenges. We have previously described the development of biocatalytic nitration processes driven by an engineered P450 TxtE fusion construct. Herein we report the creation of improved nitration biocatalysts through constructing and characterizing fusion proteins of TxtE with the reductase domain of CYP102A1 (P450BM3, BM3R). The majority of constructs contained variable linker length while one was rationally designed for optimizing protein-protein interactions. Detailed biochemical characterization identified multiple active chimeras that showed improved nitration activity, increased coupling efficiency and higher total turnover numbers compared with TxtE. Substrate promiscuity of the most active chimera was further assessed with a substrate library. Finally, a biocatalytic nitration process was developed to nitrate 4-Me-dl-Trp. The production of both 4-Me-5-NO2-l-Trp and 4-Me-7-NO2-l-Trp uncovered remarkable regio-promiscuity of nitration biocatalysts.